Media today : mass communication in a converging world - Turow, Joseph (New York: Routledge, 2023)
"This eighth edition of Joseph Turow's pathbreaking media textbook uses convergence as a lens that puts students at the center of the profound changes in the 21st century media world. It teaches students to think critically about the role of media, and what these changes mean for their lives. The book's media systems approach helps students to look carefully at how media content is created, distributed, and exhibited in the new world that the digital revolution has created. From news media to video games and social networking to mobile platforms, it provides students with the tools they need to understand and critique the media they encounter and consume. The first part examines the media world as a whole, while the second delves deep into key media industries, such as the movie, television, and video game industries. This new edition includes critical expanded coverage of social media, new forms of both audio and audiovisual media and international case studies, as well as updated figures, tables, and pedagogy, including key terms and further activities. Media Today is an excellent introduction to the world of media in the digital age, perfect for students seeking a solid grounding in media studies. Extensive pedagogical materials also make this a highly teachable book, well suited to the classroom. The accompanying website has also been updated with new student and instructor resources, including chapter recaps, recommended readings, and instructor's manual"--
Includes bibliographical references and index.
Keywords: Mass media